A New Regional Cold War? American and Chinese Posturing in the Pacific. Issue 2 (24th June 2014) - Ratuva, Steven
Abstract It is often argued that the United States and Chinese engagement in the Pacific manifests a clash of foreign policies that mimics the cold war confrontation of the post‐World War II era. The article argues that rather than a dichotomous contestation of foreign policies, the United States–China engagement is more complex in nature and needs to be understood using more 'syncretic' lenses to understand the complex synergy in their relationship, which oscillates between tension and accommodation, cooperation and competition. While there are areas of policy contestation, there are also areas of policy appeasement and convergence. This may act as a stabilising factor in the region as the two powers acknowledge the significance of the other and the long‐term cost of direct confrontation on their respective interests. This potentially contributes to a 'stable' environment where the Pacific Island Countries are prevented from taking sides, which could potentially exacerbate tension and regional instability.